Development of Community-Based Drinking Water Infrastructure in Langkat Regency - Refianda Nasution; Abdi Sugiarto; Cut Nuraini (CV. Doki Course and Training, 2026)
This study aims to analyze the condition of access to drinking water and the implementation of community-based drinking water infrastructure development programs in langkat regency, as well as to identify factors influencing their success and failure. the research employs a descriptive qualitative method, with data collection techniques including field observations, interviews with kpspams managers and village government officials, and documentation studies of data from bps, pamsimas, and the ministry of public works and housing (pupr). the results show that the level of access to safe drinking water in langkat regency remains at 78.5%, which is lower than the provincial average (82.1%) and the national average (90.7%). the pamsimas program has contributed to expanding water services; however, approximately 25–30% of the facilities have experienced functional decline or are no longer operational. the main factors influencing the operational success of the facilities include community participation, management institutions, village government support, and the sustainability of raw water sources. this study recommends a collaborative–participatory community-based drinking water management model, incorporating a mixed financing scheme, institutional legality based on village regulations, and transparent supervision. this model is considered the most relevant approach for creating equitable, independent, and sustainable drinking water services in langkat regency.